Neoadjuvant ipilimumab (3 mg/kg or 10 mg/kg) and high dose IFN-α2b in locally/regionally advanced melanoma: safety, efficacy and impact on T-cell repertoire. Issue 1 (23rd October 2018) - Tarhini, Ahmad; Lin, Yan; Lin, Huang; Rahman, Zahra; Vallabhaneni, Priyanka; Mendiratta, Prateek; Pingpank, James F.; Holtzman, Matthew P.; Yusko, Erik C.; Rytlewski, Julie A.; Rao, Uma N. M.; Ferris, Robert L.; et al.
Abstract : Background: Neoadjuvant immunotherapy utilizing novel combinations has the potential to transform the standard of care for locally/regionally advanced melanoma. We hypothesized that neoadjuvant ipilimumab in combination with high dose IFNα2b (HDI) is safe and associated with durable pathologic complete responses (pCR). Methods: Patients with locally/regionally advanced melanoma were randomized to ipilimumab 3 or 10 mg/kg × 4 doses bracketing definitive surgery, then every 12 weeks × 4. HDI was given concurrently. We evaluated the safety and efficacy of the combination with ipilimumab 3 or 10 mg/kg. The impact on T-cell fraction and clonality were investigated in tumor and blood. Results: Thirty patients (age 37–76), 15 each at 3 and 10 mg/kg, 18 male and 12 female were treated. Considering immune related adverse events (irAEs) of interest, more grade 3/4 irAEs were seen with ipilimumab 10 mg/kg versus 3 mg/kg ( p  = 0.042). Among 28 evaluable patients, 11 relapsed, of whom 5 died. Median follow-up for 17 patients who have not relapsed was 32 months. The radiologic preoperative response rate was 36% (95% CI, 21–54); 4 patients at ipilimumab 3 mg/kg and 6 at 10 mg/kg and 2 (at 10 mg/kg) later relapsed. The pCR was 32% (95% CI, 18–51); 5 patients at ipilimumab 3 mg/kg and 4 at 10 mg/kg and one (at 3 mg/kg) had a late relapse. In patients with pCR, T-cell fraction was significantly higher when measured in primary melanoma tumors ( p  = 0.033). Higher tumor T-cell clonality in primary tumor and more so following neoadjuvant therapy was significantly associated with improved relapse free survival. Conclusions: Neoadjuvant ipilimumab-HDI was relatively safe and exhibited promising tumor response rates with an associated measurable impact on T-cell fraction and clonality. Most pCRs were durable supporting the value of pCR as a primary endpoint in neoadjuvant immunotherapy trials. Trial registration: ClinicalTrials.gov, NCT01608594 . Registered 31 May 2012.